47th AIAA Fluid Dynamics Conference 2017
DOI: 10.2514/6.2017-3641
|View full text |Cite
|
Sign up to set email alerts
|

DNS of a Spatially Developing Turbulent Mixing Layer from Co-flowing Laminar Boundary Layers

Abstract: Understanding the development of a turbulent mixing layer is essential for various aerospace applications. In particular, experiments found that the flow development is highly sensitive to inflow conditions, which are difficult to reproduce in the flow simulations. In previous direct numerical simulations (DNS) of temporarily and spatially developing turbulent mixing layers, idealized inflow conditions based on mathematical approximations of the mean velocity profile were used to facilitate turbulent flow cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 32 publications
(58 reference statements)
3
15
0
Order By: Relevance
“…Understanding uncertainty in DNS results will add a value to the dataset. The current paper continues our previous effort [14] in this direction.…”
Section: Introductionsupporting
confidence: 56%
See 4 more Smart Citations
“…Understanding uncertainty in DNS results will add a value to the dataset. The current paper continues our previous effort [14] in this direction.…”
Section: Introductionsupporting
confidence: 56%
“…In particular, studies of a spatially developing two-dimensional mixing layer [15] and a temporarily evolving three-dimensional mixing layer [16] showed that the nature and magnitude of flow perturbations imposed at the inflow strongly affect the flow development and turbulence statistics. When co-flowing boundary layers separated by a splitter plate are used as inflow conditions in simulations of a spatially developing mixing layer, the plate thickness at the trailing edge and the T trailing edge shape have a significant effect on the flow features and turbulence intensity [14,17]. Results of DNS were also found to be sensitive to the spanwise size of the computational domain [14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations